PARTISIPASI POLITIK MAHASISWA - Dian Iskandar (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2022)
This Article aims to describe the mode of student political participation through conventional and unconventional forms of participation and what encourages students to participate. To achieve this goal, researchers use a descriptive quantifiable method with students of Palangka Raya University as a sample. Questionnaires are an instrument in data collection deployed using the Google Form. The result of the research on the mode of student political participation is the spectators. The trend that develops through the form of participation is passive supportive because students are more likely to participate regularly in elections. On the other hand, it is known that personal goals and self-awareness of civic duty are the main factors of students' interest in politics